KORELASI ANTARA RADIASI MATAHARI DAN INTENSITAS PENYAKIT BUSUK PELEPAH PADA TANAMAN PADI DI LAHAN RAWA KECAMATAN JEJANGKIT KABUPATEN BARITO KUALA - Eka Rismawina; Salamiah Salamiah; Dewi Erika Adriani (EnviroScienteae, 2021)
Sheath rot disease can affect the development of panicles so that it might reduce rice production and productivity. Nevertheless, the disease has not been widely discussed as a rice plant disease in South Kalimantan, thus it is necessary to conduct research on sheath rot disease related to the microclimate, in this case solar radiation as a part of the environmental factors for rice cultivation. The method used in this study was the quantitative survey on the ULM Action Research Program area, that is observation on samples and populations in the research area.  Data were collected using the purposive sampling method,  by using research instruments, namely three large plots measuring 140 m2 (10 m x 14 m) in 1 ha of land planted with rice. Each plot was divided into 15 subplots.  Intensity data of sheath rot disease were taken from 5 samples in each subplot.  The number of sample units taken in this study was 5 samples x 45 subplot = 225 samples.  The weather station telemetry for measuring solar radiation (Wm-2) was installed at the altitude of 60 cm and 120 cm from the plant canopy.  The highest disease intensity of sheath rot on stems was 0.45% and sheath rot on panicles was 12.72%.  Solar radiation at the altitude of 120 cm has an effect to the intensity of sheath rot disease in panicle; that is, each increase of one unit of solar radiation (Wm-2) will reduce the intensity of sheath rot disease in panicles by 2.651%.